Peran Mediasi Komitmen Guru Terhadap Kinerja: Pengaruh Budaya Organisasi, dan Motivasi - Soelistya, Djoko; Mubarok, Husni; Agustina, Heni; Syamlan, Adiba Fuad (BALANCE: Economic, Business, Management and Accounting Journal, 2023)
ABSTRACTThe problem is that teacher performance could be more optimal, but the existing organizational Culture is well implemented, and teacher motivation is carried out according to organizational instructions. The research aims to analyze the role of mediating teacher commitment to performance which is influenced by organizational Culture and motivation. This research is quantitative, and the population is 60 respondents with SmartPLS 3.0 analysis. The results show (1) Organizational Culture has an effect on teacher performance; (2) Organizational Culture has no effect on teacher commitment; (3) Motivation has an effect on teacher commitment; (4) Motivation has an effect on teacher performance; (5) Teacher commitment has an effect on teacher performance ; (6) Organizational culture can directly affect teacher performance, even without the mediation of teacher commitment; (7) Motivation can affect teacher performance directly even without the mediation of teacher commitment, so the organizational Culture that educational institutions have given is still carried out consistently and is preserved, and its harmony with teachers and good teacher motivation needs to be maintained by giving teachers the confidence to can explore their competence in carrying out their duties.ABSTRAK Permasalahan kinerja guru yang belum optimal, tetapi budaya organisasi yang ada sudah diterapkan dengan baik, dan motivasi guru dijalankan sesuai petunjuk organisasi. Tujuan penelitian menganalisis peran mediasi komitmen guru terhadap kinerjanya yang dipengaruhi oleh budaya organisasi dan motivasinya. Penelitian ini kuantitatif dan populasi sebanyak 60 responden dengan analisis SmartPLS 3.0. Hasil menunjukan (1) Budaya Organisasi berpengaruh terhadap kinerja guru; (2) Budaya Organisasi tidak berpengaruh terhadap komitmen guru; (3) Motivasi berpengaruh terhadap komitmen guru; (4) MotivasiÂ  berpengaruh terhadap kinerja guru; (5) Komitmen Guru berpengaruh terhadap kinerja guru; (6) Budaya Organisasi dapat mempengaruhi kinerja guru secara langsung, walaupun tanpa mediasi komitmen guru; (7) Motivasi dapat mempengaruhi kinerja guru secara langsung walaupun tanpa mediasi komitmen guru, jadi budaya organisasi yang sudah diberikan oleh lembaga pendidikan tetap dijalankan secara konsisten dan dilestarikan serta keharmonisannyaÂ  terhadap para guru, serta motivasi guru yang sudah baik perlu dipertahankan dengan memberikan kepercayaan guru untuk bisa mengexplore kompetensinya dalam menjalankan tugasnya.